Direct and indirect effects of perception on generalization gradients. (March 2019) - Zaman, Jonas; Ceulemans, Eva; Hermans, Dirk; Beckers, Tom
Abstract: For more than a century, researchers have attempted to understand why organisms behave similarly across situations. Despite the robust character of generalization, considerable variation in conditioned responding both between and within humans remains a challenge for contemporary generalization models. The current study aims to investigate the extent to which variation in behavior in a context of generalization can be attributed to differences in perception. We combined a fear conditioning and generalization procedure with a perceptual decision task in humans. We found that the failure to perceive a novel stimulus as different from the trained fear-evoking stimulus led to increased conditioned responding. Furthermore, perceptual errors yielded perceived stimulus-outcome contingencies that differed substantially from the objective contingencies. Final, the impact of a perceptual error was dependent upon these perceived contingencies. These findings suggest that generalization across a perceptual dimension is to a large extent driven by perceptual errors that directly affect behavior but also indirectly as they yield different learning experiences between individuals. Highlights: The role of perception on generalized responding was investigated. A generalization protocol was extended with a perceptual decision task. Perceptual errors led to increased conditioned responding. Perceptual errors led to different learning experiences between individuals. Perceptual generalization is to a large extent driven by perceptual errors.